AN OUTBREAK OF BOTULISM AMONG SHEEP AND GOATS IN NORTHERN LOCALITIES OF NORTH KORDOFAN STATE, SUDAN - Ibrahim, A.A.; Shigidi, M.T.A. (Journal of Veterinary Medicine and Animal Production, 2021)
The study reports the results of an investigation of an outbreak of a disease in sheep and goats in the northern localities of North Kordofan State which was diagnosed on clinical signs to be botulism. One hundred and thirty four out of 3480 sheep and goats under natural grazing, were affected within a month time. Field investigation was made to collect information about the disease by interviewing the owners. Necropsy was made on 9 fresh carcasses of dead animals. Toxin neutralization test in mice detected Type C botulinum toxin in 1 of 10 serum samples, in 1 of 9 samples of rumenal contents from dead animals, and in 3 of 6 bones and muscle tissues from carcasses. The test confirmed Clostridium botulinum Type C toxin to be the possible cause of the outbreak.